1974
DOI: 10.1017/s000748530004089x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of parasites and predators on the cereal aphids Metopolophium dirhodum (Wlk.) and Macrosiphum avenae (F.) (Hem., Aphididae)

Abstract: In a study of aphids and their parasites, hyperparasites and predators in a field of cereals at Rothamsted Experimental Station in 1970-71, samples were taken by counting specimens in 0-3-m lengths of row and by means of a suction trap set 12-2 m above ground and 0-5 km away from the field. Migrant aphids (Metopolophium dirhodum (Wlk.) and Macrosiphum avenae (F.)) and Braconid parasites (Aphidius spp., Ephedrus plagiator (Nees) and Praon volucre (Hal.)) were caught from April-May to August-September, with most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
43
2
1

Year Published

1975
1975
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 16 publications
4
43
2
1
Order By: Relevance
“…Similarly, Dean (1974) caught large numbers of migrating cereal aphid primary parasitoids in 12-2 m high suction traps during the summer. Using a multiple regression analysis model, we could show that the decrease in aphid primary parasitism between the maximum level and the level recorded 1 week later was correlated with the degree of hyperparasitism at the time of greatest primary parasitism.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Dean (1974) caught large numbers of migrating cereal aphid primary parasitoids in 12-2 m high suction traps during the summer. Using a multiple regression analysis model, we could show that the decrease in aphid primary parasitism between the maximum level and the level recorded 1 week later was correlated with the degree of hyperparasitism at the time of greatest primary parasitism.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite some evidence that the presence of flowers increases biological control by hoverfly larvae (Hickman & Wratten, 1996;White, Wratten, Berry, & Weigmann, 1995), the experimental evidence for a direct link between hoverfly oviposition rates and the presence of flowers is still conflicting (Dean, 1974). The investigations of Fluke (1937), for example, suggested that there was a direct relationship between the abundance of flowers and hoverfly oviposition rates in fields with or without flowers.…”
Section: Introductionmentioning
confidence: 99%
“…Some day-time observations suggest that predators such as Araneae and Staphylinidae are scarce on cereal plants (e.g. Dean 1974) but these can be misleading if such arthropods are only active and/or present on the vegetation at night. Similarly, predation by some species may be underestimated if feeding is nocturnal and sampling diurnal.…”
Section: Introductionmentioning
confidence: 99%